Acao antioxidante de extratos de alecrim (Rosmarinus officinalis L.) em files de peixes da especie pacu (Piaractus mesopotamicus Holmberg) - Sant'Ana, L. S. [UNESP]; Mancini-Filho, J. [UNESP] (My University, 1999)
The antioxidant effect of plant extract has been an interesting issue for many researchers in past few years. Spices have been identified as products with large amounts of antioxidants, and rosemary is one the most studied spice. Studies have shown evidences that population with high intake of these substances have less incidence of coronary heart disease. The objective of this work was verify the antioxidant action of the commercial rosemary oleoresin Herbalox® (used to feed the pacu (Piaractus mesopotamicus) fish. The juveniles pacu were fed with isocaloric and isoproteic diets, for two groups the lipid source was soybean oil and for the another it was corn oil. For each group of the different lipid sources, rosemary extract Herbalox® (were added in one lot and on the other which was used as control. The results showed that the addition of rosemary extracts to the ration protected them against peroxidation, when compared with the control, the lipid source also have influence on these protection.
Antioxidant action of rosemary extract (Rosmarinus officinalis L.) in 'Pacu' (Piaractus mesopotamicus Holmberg) fillets
Keywords: Antioxidants; Fish pacu; Lipid oxidation; Piaractus mesopotamicus Holmberg; Rosemary extracts; Rosmarinus officinalis L.; antioxidant; corn oil; herbalox; resin; Rosmarinus officinalis extract; unclassified drug; antioxidant activity; dietary intake; fish; food intake; heart protection; ischemic heart disease; lipid oxidation; spice; Glycine max; Piaractus mesopotamicus; Rosmarinus officinalis; Zea mays